Clinical features of chronic kidney disease in dogs with the serological presence of Leptospira spp., Ehrlichia canis, and Anaplasma phagocytophilum - Claire A. Vázquez-Manzanilla; María F. Cárdenas-Marrufo; Eduardo Gutiérrez-Blanco; Matilde Jiménez-Coello; Nelly R. Pech-Sosa; Antonio Ortega-Pacheco (BMC, 2023)
Abstract Chronic kidney disease is commonly diagnosed in dogs, and clinical signs may be aggravated when infected agents are involved. In this case report, 33 dogs with chronic kidney disease were clinically evaluated and serologically tested for Leptospira spp., Ehrlichia canis, and Anaplasma phagocytophilum. The seroprevalence for Leptospira spp. was 39.4%. The most frequent serovars found were Pyrogenes, Canicola, Bratislava and Australis, with serological titers between 1:100 to 1:800. Clinical signs included fever, depression, decreased body condition, vomiting and hematuria. Significant laboratory findings were anemia, leukocytosis, thrombocytopenia, increased liver enzymes, urea and creatinine, hyperbilirubinemia and hyperphosphatemia. All leptospira seronegative dogs were positive for one or both monitored homoparasites (i.e., E. canis and A. phagocytophilum); only three leptospira seropositive dogs were positive for one or both hemoparasites. Findings also suggest that endemic hemoparasites of dogs should be monitored in dogs with a kidney condition for a better clinical picture of the patients and therapeutic approach.